Carles Salvador, l’autoritat gramatical - Pitarch, Vicent (Caplletra. Revista Internacional de Filologia, 2015)
Carles Salvador had strong nationalistic convictions and was very active in promoting the Catalan language in several areas, specifically in developing treatises on spelling, grammar and lexicography. His work would help consolidate the standardization of Catalan in the Valencian Country and would make him an unquestionable authority on Catalan grammar.